Broadband S-Parameter-Based Characterization of Multilayer Ceramic Capacitors Submitted to Mechanical Stress Through Bending Tests on a PCB - Victoria Gutiérrez-Vicente; Jesús Alejandro Torres-Torres; Reydezel Torres-Torres (Micromachines)
A full characterization of multilayer ceramic capacitors including variations in capacitance, series resistance, and series inductance is accomplished by measuring their RF response while being submitted to mechanical stress. This allows for the first time quantifying the degradation of the device’s RF performance when cracks form within its structure. In this regard, the main challenge is designing an interface for measuring the high-frequency response of a capacitor using a vector network analyzer as a bending test on a PCB in progress, which is achieved here by using a microstrip-based test fixture. The results indicate that there is an overestimation of its response to microwave stimuli when considering only the degradation impact as a reduction in capacitance. Capacitors of representative sizes and capacitances are analyzed to show the usefulness of the proposal, whereas the validity of the results is verified by observing the correlation with measurements collected using microprobes and performing optical inspections of cross-sectioned samples.